Effectiveness of Village Fund Management: A Case Study in Bone District, South Sulawesi - Bustang; Akhmad; Lukman Hakim (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
This paper aims to determine the effectiveness of the Village Fund management in Sibulue District, Bone Regency, South Sulawesi Province. With Village Funds, village governments are given sufficient authority and resources to improve the economy and the welfare of rural communities. The results of the study show that the use of village funds is quite good and effective to develop the economic potential of the village. The main problem that arises in the management of village funds is the lack of knowledge of human resources related to village financial planning and management.